How surface acting affects turnover intention among family doctors in rural China: the mediating role of emotional exhaustion and the moderating role of occupational commitment - Anqi Wang; Changhai Tang; Lifang Zhou; Haiyuan Lv; Jia Song; Zhongming Chen; Wenqiang Yin (BMC, 2023)
Abstract Background Family doctors in rural China are the main force for primary health care, but the workforce has not been well stabilized in recent years. Surface acting is an emotional labor strategy with a disparity between inner feelings and emotional displays, provoking negative effects such as emotional exhaustion, occupational commitment reduction, and, consequently, increasing turnover rate. With the Conservation of Resources theory, this study explores how the surface acting of rural family doctors affects turnover intention through emotional exhaustion and investigates what role occupational commitment plays in this relationship. Methods With a valid response rate of 93.89%, 953 valid data were collected by an anonymous self-administered questionnaire survey in December 2021 in Shandong Province, China. Cronbach's Alpha and confirmatory factor analysis (CFA) were used to estimate reliability and construct validity, respectively. The PROCESS macro in SPSS was performed to analyze the mediating and moderated mediation effects of surface acting, emotional exhaustion, occupational commitment, and turnover intention. Results Reliability and validity indicated that the measurement instruments were acceptable. Surface acting had a direct positive effect on turnover intention (β = 0.481, 95% CI [0.420, 0.543]). Emotional exhaustion partially mediated the effect of surface acting on turnover intention (indirect effect: 0.214, 95% CI [0.175, 0.256]). Occupational commitment moderated the effect of emotional exhaustion on turnover intention (β = − 0.065, 95% CI [− 0.111, − 0.019]), and moderated the indirect effect of surface acting on turnover intention via emotional exhaustion (index of moderated mediation: − 0.035). Conclusions Emotional exhaustion partially mediates the relationship between surface acting and turnover intention among family doctors in rural China, and occupational commitment moderates the direct effect of emotional exhaustion on turnover intention and further moderates the mediating effect. Policymakers should pay more attention to the effects of emotional labor and emotional resource depletion on the stability of rural health human resources.